Building resilient future: information technology and disaster management - a Malaysian perspective - Abid, Sheikh Kamran; Sulaiman, Noralfishah; Chan, Shiau Wei; Nazir, Umber (2021)
The recent evets of flooding, earthquakes, uncontrolled wildfires, hurricanes, and deadly storms in world has considered a serious threat to mankind and preparing for devastating disasters has never been more critical and urgent. Emergency Events Database suggests that by year 2050 the damages to flood related incidents to coastal cities will cost near to US$1 trillion. Risk from acts of nature cannot be fully prevented but needs to minimize and safe the innocent lives and property by utilizing disaster management technique to mitigate the losses. This paper presents Information Technologies applications in disaster management phases such as Mitigation, Preparedness, Response and Recovery. Geographic Information System, Remote Sensing, mobile technology, drone, and satellite imagery and MOBILISE analytic platform considered as effective and efficient ways of strengthening resilience when disaster strikes and tremendously helpful for coordinating responses and accelerating the recovery of individuals and communities in the aftermath of recent natural disasters.